Factors Affecting the Indirect Costs of Accidents to the Employees of Urban Rail Infrastructure Projects - Farrita Mohd Kamar, Izatul; Che Ahmad, Asmalia; Mohd Derus, Mohmad; Yusof Kasiron, Mohd (International Journal of Engineering and Technology, 2018)
Construction activities stand as unique because most of the activities take place outdoors and under conditions that are not conducive to safety and health. The work injuries can create economic issues for the society. The stakeholders ignore the cost of an accident without realising its impacts on the industry and the country. Hence, this paper has determined the relationship between the indirect costs of the accident and the factors influencing these costs to the employee via a questionnaire survey. For this research, the employee, also known as a worker, is the person who is injured at the workplace. Multiple regression was performed on the sixty-two (62) accident cases from the MRT 1 SBK (Sungai Buloh-Kajang) Line Projects. The finding shows that the types of accident classifications, the day of the stop work order, day of the hospital admission, day of the medical leave and location of the body’s injuries significantly affected the total indirect costs of the accident to the employee. These findings could heighten the importance of the effect of an accident on the Employer’s awareness in improving preventive measures for a construction project.